Quantitative mapping of microtubule-associated protein 2c (MAP2c) phosphorylation and regulatory protein 14-3-3ζ-binding sites reveals key differences between MAP2c and its homolog Tau - Jansen, Séverine; Melková, Kateřina; Trošanová, Zuzana; Hanáková, Kateřina; Zachrdla, Milan; Nováček, Jiří; Župa, Erik; Zdráhal, Zbyněk; Hritz, Jozef; Žídek, Lukáš (The Journal of biological chemistry, 2017)
Microtubule-associated protein 2c (MAP2c) is involved in neuronal development and is less characterized than its homolog Tau, which has various roles in neurodegeneration. Using NMR methods providing single-residue resolution and quantitative comparison, we investigated molecular interactions important for the regulatory roles of MAP2c in microtubule dynamics. We found that MAP2c and Tau significantly differ in the position and kinetics of sites that are phosphorylated by cAMP-dependent protein kinase (PKA), even in highly homologous regions. We determined the binding sites of unphosphorylated and phosphorylated MAP2c responsible for interactions with the regulatory protein 14-3-3ζ. Differences in phosphorylation and in charge distribution between MAP2c and Tau suggested that both MAP2c and Tau respond to the same signal (phosphorylation by PKA) but have different downstream effects, indicating a signaling branch point for controlling microtubule stability. Although the interactions of phosphorylated Tau with 14-3-3ζ are supposed to be a major factor in microtubule destabilization, the binding of 14-3-3ζ to MAP2c enhanced by PKA-mediated phosphorylation is likely to influence microtubule-MAP2c binding much less, in agreement with the results of our tubulin co-sedimentation measurements. The specific location of the major MAP2c phosphorylation site in a region homologous to the muscarinic receptor-binding site of Tau suggests that MAP2c also may regulate processes other than microtubule dynamics.
Keywords: vazba proteinů; proteiny tau; 14-3-3 protein; proteiny asociované s mikrotubuly; Mass Spectrometry; 14-3-3 Proteins; mikrotubuly; Protein Binding; Amino Acid Motifs; krysa rodu Rattus; mass spectrometry (MS); Kinetics; Neurons; Phosphorylation; Cyclic AMP-Dependent Protein Kinases; Signal Transduction; Binding Sites; neurony; kinetika; fosforylace; proteiny 14-3-3; tau Proteins; Magnetic Resonance Spectroscopy; signální transdukce; Microtubules; protein kinase A (PKA); Microtubule-Associated Proteins; nuclear magnetic resonance (NMR); zvířata; proteinkinasy závislé na cyklickém AMP; microtubule-associated protein (MAP); Rats; Tubulin; Animals; aminokyselinové motivy; magnetická rezonanční spektroskopie; tubulin; hmotnostní spektrometrie; vazebná místa